The Use of Quercetin to Improve the Antioxidant and Regenerative Properties of Frozen or Cryopreserved Human Amniotic Membrane - Valeria Purpura; Serena Benedetti; Elena Bondioli; Francesca Scarpellini; Agnese Giacometti; Maria Cristina Albertini; Davide Melandri (MDPI AG, 2022)
The biological properties of the human amniotic membrane (HAM) and its characteristic ability to be a reservoir of growth factors promoting wound healing make it an ideal biological dressing for the treatment of different clinical conditions, such as burns and non-healing wounds. However, the application of a preservation method on the HAM is required during banking to maintain biological tissue properties and to ensure the release overtime of protein content for its final clinical effectiveness after application on the wound bed. Although cryopreservation and freezing are methods widely used to maintain tissue properties, reactive oxygen species (ROS) are produced within tissue cellular components during their switching from frozen to thawed state. Consequently, these methods can lead to oxidative stress-induced cell injury, affecting tissue regenerative properties and its final clinical effectiveness. Taking advantage of the antioxidant activity of the natural compound quercetin, we used it to improve the antioxidant and regenerative properties of frozen or cryopreserved HAM tissues. In particular, we evaluated the oxidative damage (lipid peroxidation, malondialdehyde) as well as the regenerative/biological properties (bFGF growth factor release, wound healing closure, structure, and viability) of HAM tissue after its application. We identified the effectiveness of quercetin on both preservation methods to reduce oxidative damage, as well as its ability to enhance regenerative properties, while maintaining the unaltered structure and viability of HAM tissue. The use of quercetin described in this study appears able to counteract the side effects of cryopreservation and freezing methods related to oxidative stress, enhancing the regenerative properties of HAM. However, further investigations will need to be performed, starting from these promising results, to identify its beneficial effect when applied on burns or non-healing wounds.